Meningkatkan Motivasi Warga Untuk Kesadaran Gotong Royong Dalam Membangun Desa Tanjung Tambak Baru Kabupaten Ogan Ilir - Yuniar Yuniar; Ibrahim Ibrahim; Amilda Amilda; Megawati Megawati; Alvi Delta Viani (Universitas Indraprasta PGRI, 2023)
This community education program is based on the collaboration of real work college students in Tanjung Tambak Baru Village, Tanjung Batu District, Ogan Ilir Regency. The purpose of this service is to provide awareness to the public to maintain cleanliness more. The UIN Palembang KKN program in carrying out programs to increase community motivation through mutual cooperation activities in building the East Santapan village has been implemented, community awareness will build a better village, still needs to work hard and there needs to be participation from the Government, especially the Santapan Timur village government, as well other stakeholders. Public awareness is still low, it is necessary to implement a good program in building an independent village. The village government has tried through several activities such as mutual cooperation, instilling motivation in life as well as other activities by involving existing elements in the education process for the community, such as the involvement of this UIN Raden Fatah Palembang KKN student.